Gellan gum-based mucoadhesive microspheres of almotriptan for nasal administration: Formulation optimization using factorial design, characterization, and in vitro evaluation - Zaheer Abbas; Sachin Marihal (Wolters Kluwer Medknow Publications, 2014)
Background: Almotriptan malate (ALM), indicated for the treatment of migraine in adults is not a drug candidate feasible to be administered through the oral route during the attack due to its associated symptoms such as nausea and vomiting. This obviates an alternative dosage form and nasal drug delivery is a good substitute to oral and parenteral administration. Materials and Methods: Gellan gum (GG) microspheres of ALM, for intranasal administration were prepared by water-in-oil emulsification cross-linking technique employing a 2 3 factorial design. Drug to polymer ratio, calcium chloride concentration and cross-linking time were selected as independent variables, while particle size and in vitro mucoadhesion of the microspheres were investigated as dependent variables. Regression analysis was performed to identify the best formulation conditions. The microspheres were evaluated for characteristics such as practical percentage yield, particle size, percentage incorporation efficiency, swellability, zeta potential, in vitro mucoadhesion, thermal analysis, X-ray diffraction study, and in vitro drug diffusion studies. Results: The shape and surface characteristics of the microspheres were determined by scanning electron microscopy, which revealed spherical nature and nearly smooth surface with drug incorporation efficiency in the range of 71.65 ± 1.09% - 91.65 ± 1.13%. In vitro mucoadhesion was observed the range of 79.45 ± 1.69% - 95.48 ± 1.27%. Differential scanning calorimetry and X-ray diffraction results indicated a molecular level dispersion of drug in the microspheres. In vitro drug diffusion was Higuchi matrix controlled and the release mechanism was found to be non-Fickian. Stability studies indicated that there were no significant deviations in the drug content, in vitro mucoadhesion and in vitro drug diffusion characteristics. Conclusion: The investigation revealed promising potential of GG microspheres for delivering ALM intranasally for the treatment of migraine.